Estudo do comportamento no estado fresco e endurecido do concreto com incorporação de resíduo de corte de botão - Avelino, Veruska Kelly Gomes Rocha (2011)
This works aims at investigating the effects of adding waste from RCBP-polyester button manufacturing to Portland cement concrete, particularly regarding its consistency and mechanic strength. The RCBP used came from a button factory located in Parnamirim, RN, Brazil. The waste was added to the concrete on different ratios: 5 %, 10 %, 15 % and 20 % of the total cement mass. A sample of concrete without the RCBP was used as reference, 1:1,33:2,45:0,50. For the mechanic strength test four samples were tested with different ages (3, 7 and 28 days old) and mixtures. Furthermore, a Slump Test was also conducted in order to verify the concrete s consistency. A tendency to a reduction in the compression resistance was noticed for all samples. For the samples with 5 % and 10 %, there was also an increase in the traction resistance during inflexion, regarding the reference concrete. In the microstructural analysis, the RBCP was observed to show an irregular and porous surface, thus explaining the consistency decrease